37P Chemokine receptor CCR2b expressing anti-Tn-MUC1 CAR-T cells enhanced anti-breast cancer activity. (15th December 2019) - Lin, Y; Yin, H; An, H; Zhou, C; Zhou, L; Chen, S; McGowan, E
Abstract: Background: Enhanced anti-tumour activity is required for eradication of solid tumours by CART cells. One possibility of enhancing anti-tumour activity is by programming CART cells to express chemokine receptors that match chemokines produced either by the tumours or tumour-associated cells, thereby improving the infiltrating capacity of the CART cells. In this study, we engineered CCR2b expressing anti-Tn-MUC1 CAR T cells for the treatment of breast cancer. Methods: Anti-Tn-MUC1-CARs were constructed using the SM3 scFv. Following lenti-MUC1 CAR retroviral transduction, efficiency of transgenic expression was assessed by flow cytometry. CCR2b expressing anti-Tn-MUC1 CAR T cells were prepared using PLV-CAR-5E5-CCR2b lentivirus. The susceptibility of MCF-7 cells to either anti-MUC1 CART or CCR2b expressing anti-MUC1 CART cell-mediated lysis was assessed using in vitro killing assays. For cytolytic analysis, CART-cells were cocultured 10:1 (effector:target) ratio with MCF-7 cells. The effects of CCR2b expressing CART cells on anti-tumour activity and infiltration were also assessed in an in vivo murine xenograft model. Results: Activated T cells co-modified with both CCR2b and anti-MUC1-CAR had greater anti-tumour activity both in vivo and in vitro. When the effector / target cell ratio was 10, the killing rates of CART and CART-CCR2b were 56.9% and 83.9%, respectively. Tumour size was significantly smaller (P < 0.001) in the CAR-CCR2b group compared to the CAR alone group. At day 7 post-injection of CART cells, the infiltrated T cells was significantly increased (∼2 folds) in the CAR-CCR2b group compared with the CART only group. Conclusion: Our data demonstrated that the anti-tumour activity of the CCR2b expressing anti-Tn-MUC1 CART cells is 1.5 times more potent than CART cells without CCR2b. Augmentation of tumour suppression was also demonstrated in vivo in a murine xenograft model. These pre-clinical results show translational potential to the clinic for treatment of solid breast tumours. Legal entity responsible for the study: Guangzhou Anjie Biomedical Technology Co. Ltd. Funding: Guangzhou Anjie Biomedical Technology Co. Ltd. Disclosure: All authors have declared no conflicts of interest.